The Impact of the Global Financial Crisis on Youth Labour Markets - Pramod N. (Raja) Junankar (Institute for the Study of Labor (IZA), 2014)
This paper investigates the impact of the GFC on youth unemployment and long term unemployment. In particular, we study whether the GFC had a bigger impact on youths than adults, and whether youth unemployment rates increased due to an increase in youth wages relative to adult wages. To anticipate our results, we find that the youth unemployment rates increased significantly more than that of adults even though youth wages had been falling relative to adult wages.
Keywords: J64; J21; 330; youth labour markets; youth unemployment; global financial crisis